Effect of Rumensin on the growth and sexual development of beef bulls - L.R. Corah; W.D. Busby; R.M. McKee; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1981)
Fifty percentage Simmental bull calves were fed either with or without Rumensin. Although Rumensin improved gain by 9.2%, it had no effect on sexual development.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Growth; Sexual development; Bulls